Amygdala Nuclei Volumes Are Selectively Associated With Social Network Size in Homeless and Precariously Housed Persons - Jones, Paul W.; Thornton, Allen E.; Jones, Andrea A.; Knerich, Verena M.; Lang, Donna J.; Woodward, Melissa L.; Panenka, William J.; Su, Wayne; Barr, Alasdair M.; Buchanan, Tari; Honer, William G.; Gicas, Kristina M. (Frontiers in Behavioral Neuroscience, 2020)
Objective: The amygdala is a brain region comprised of a group of functionally distinct nuclei that play a central role in social behaviour. In homeless and precariously housed individuals, high rates of multimorbidity and structural aspects of the environment may dysregulate social functioning. This study examined the neurobiological substrates of social connection in homeless and precariously housed persons by examining associations between amygdala nuclei volumes and social network size. Methods: Sixty participants (mean age 43.6 years; 73.3% male) were enrolled from an ongoing study of homeless and precariously housed adults in Vancouver, Canada. Social network size was assessed using the Arizona Social Support Interview Schedule. Amygdala nuclei volumes were extracted from anatomic T1-weighted MRI data. The central and basolateral amygdala nuclei were selected as they are implicated in anxiety-related and social behaviors. The hippocampus was included as a control brain region. Multivariable regression analysis investigated the relationship between amygdala nuclei volumes and social network size. Results: After controlling for age, sex, and total brain volume, individuals with larger amygdala and central nucleus volumes had a larger network size. This association was not observed for the basolateral amygdala complex, though subsequent analysis found the basal and accessory basal nuclei of the basolateral amygdala were significantly associated with social network size. No association was found for the lateral amygdala nucleus or hippocampus. Conclusions: These findings suggest that select amygdala nuclei may be differentially involved in the social connections of persons with multimorbid illness and social marginalization.